(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This study evaluates the effectiveness of using change management methodologies to improve employee adoption of new Electronic Healthcare Systems (EHS) in the Kingdom of Saudi Arabia (KSA). The research identifies three primary categories of barriers to EHS implementation: technical, organizational, and human factors. Technical challenges include system compatibility issues, data integration problems, and security concerns. Organizational barriers encompass large capital requirements, process redesign, and alignment with strategic goals. Human factors involve resistance to change and the need for continuous training and support. The study aims to assess the current status of EHS adoption, identify the types of EHS being implemented, and examine the factors influencing their adoption. It also investigates the major challenges hindering EHS implementation and evaluates the performance of various change management approaches. The research methodology combines quantitative and qualitative methods, including surveys, interviews, focus group discussions, and document analysis. The findings indicate a positive attitude towards EHS among healthcare professionals in KSA, with change management methodologies significantly enhancing employee acceptance and reducing resistance. Effective strategies for implementation include comprehensive assessments, open communication, clear reasons for change, employee participation, and regular training and support. The study concludes that change management methodologies are crucial for the successful adoption of EHS, with improving communication and ensuring proper training and support being the most successful aspects. The overall effectiveness of these methodologies is highlighted by a positive response rate of 73.10%.